2020
DOI: 10.3390/ijms21155207
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages in Osteosarcoma: From Mechanisms to Therapy

Abstract: Osteosarcomas (OSs) are bone tumors most commonly found in pediatric and adolescent patients characterized by high risk of metastatic progression and recurrence after therapy. Effective therapeutic management of this disease still remains elusive as evidenced by poor patient survival rates. To achieve a more effective therapeutic management regimen, and hence patient survival, there is a need to identify more focused targeted therapies for OSs treatment in the clinical setting. The role of the OS tumor stroma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(145 citation statements)
references
References 172 publications
(217 reference statements)
1
116
0
Order By: Relevance
“…Although in-depth knowledge has been made in the diagnosis and treatment strategies of OS, due to its delayed diagnosis and lack of effective treatment strategies, its mortality rate remains high [ 3 , 11 ]. Therefore, it is essential to have a thorough understanding of the underlying mechanisms of OS carcinogenesis in order to develop new OS treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although in-depth knowledge has been made in the diagnosis and treatment strategies of OS, due to its delayed diagnosis and lack of effective treatment strategies, its mortality rate remains high [ 3 , 11 ]. Therefore, it is essential to have a thorough understanding of the underlying mechanisms of OS carcinogenesis in order to develop new OS treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Not only mifamurtide (by promoting a TAM polarization towards an intermediate M1/M2 phenotype), but also all trans retinoic acid, esculetin, zoledronate, natalizumab, nivolumab, and pembrolizumab may have the capacity of shaping TAM polarization and their function [NR]. Recent evidence also suggests that blocking PI 3-kinase Îł, ERK5-MAPK, and c-Maf pathways (using, for example, nanoparticles loaded with its specific inhibitors) may promote repolarization of TAM to an M1 phenotype with subsequent antitumor and anti-metastatic effects [ 94 ]. Finally, the use of chimeric antigen receptor macrophages may also have positive effects on TAM polarization [ 94 ] [NR].…”
Section: Immunotherapymentioning
confidence: 99%
“…Recent evidence also suggests that blocking PI 3-kinase Îł, ERK5-MAPK, and c-Maf pathways (using, for example, nanoparticles loaded with its specific inhibitors) may promote repolarization of TAM to an M1 phenotype with subsequent antitumor and anti-metastatic effects [ 94 ]. Finally, the use of chimeric antigen receptor macrophages may also have positive effects on TAM polarization [ 94 ] [NR].…”
Section: Immunotherapymentioning
confidence: 99%
“…One of the main challenges observed in immunotherapy is the inability to reliably predict patient response to treatment, thus there is a need for suitable biomarkers to more precisely inform treatment choices. Useful insights to achieve this goal may derive from a better understanding of the complex and heterogeneous TME characterising sarcomas [ 135 , 136 , 137 ]. A recent immunogenomic study including gene expression data from more than 850 sarcomas had identified three prognosis-related TME groups according to the extent of infiltration of 22 different immune cells [ 138 ].…”
Section: Future Directionsmentioning
confidence: 99%